Does Environmental Management Accounting Matter in Promoting Sustainable Development? A study in Iraq: Apakah Akuntansi Manajemen Lingkungan Penting dalam Mempromosikan Pembangunan Berkelanjutan? Sebuah studi di Irak - Hutman falih Chichan; Hussein kareem mohammed; Tariq Tawfeeq Yousif Alabdullah (Universitas Muhammadiyah Sidoarjo, 2021)
Purpose of this study is to examine the extent to which Iraqi industrial companies are aware of the concept of environmental management accounting (EMA), to examine the role of EMA in providing information that might influence decisions related to environmental protection and preservation of natural resources to contribute to the development of sustainable development. A sample of Iraqi industrial firms was surveyed by distributing a questionnaire to a random sample of the research community in the context of Iraqi firms. In addition, it also considers the social dimensions of sustainable development and the economy. The resolution data were analyzed using a statistical program (SPSS). When analyzing the data, the findings of the current study indicate that Iraqi industrial companies have an awareness of environmental management accounting concepts. In addition it provides information that contributes to the promotion of sustainable development. This study recommends the need to implement environmental management accounting (EMA) in Iraqi industrial companies because of its important role in providing information that leads to the reduction of negative environmental impacts resulting from the practice of its activities.